Acupuncture Use among American Adults: What Acupuncture Practitioners Can Learn from National Health Interview Survey 2007?. (22nd February 2012) - Zhang, Yan; Lao, Lixing; Chen, Haiyan; Ceballos, Rodrigo
Abstract : This paper examined the National Health Interview Survey (NHIS) 2007 and explored acupuncture users sociodemographics characteristics, reasons and the nature of acupuncture use, and the relationship of such use with conventional medical care. All individuals who completed adults core interviews (N = 23, 393) were included. Three subsets of samples (nonuser, former user, and recent user) were used in the analysis performed in Stata. Our findings revealed that ever acupuncture user (including former and recent user) increased from 4.2% to 6.3% of the population, representing 8.19 million and 14.01 million users in 2002 and 2007, respectively. We expected this trend to continue. People not only used acupuncture as a complementary and alternative approach to conventional treatment for a specific health condition, but also used it as a preventive means to promote general health. Effectiveness and safety appeared not to be the main predictors of acupuncture use; rather, awareness, cost, and insurance coverage played a bigger role in decision making.